Efforts to improve teacher competency in developing learning materials through collaborative academic supervision - Azwardi, Azwardi (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2020)
This study aims to prove collaborative academic supervision actions to improve teachers’ competence in developing learning materials as well as how collaborative academic supervision measures to achieve these goals. This research uses an action research design. This action research was carried out in the context of the school. This action research consists of cycles consisting of planning, acting, observing, and reflecting. The subjects in this study were 86 teachers in one Indonesian regent of Jambi provincial. This study was conducted in 2019/2020 academic year in the odd semester. The results of the study found that individual collaborative academic supervision actions to teachers could scientifically improve teacher competence in compiling learning materials, namely syllabus and lesson plans. This result is proven by the increase in the quality and quantity of syllabus and lesson plans assessed by teachers after collaborative academic supervision in the second cycle. The second cycle of action also resulted in an increase in teacher competency in preparing syllabi and lesson plans that were both 62% and 58%. This research recommends for the school principals that the implementation of individual collaborative supervision is very suitable to be used to improve teacher competence in developing learning materials.